Memprediksi Tingkat Penjualan Smartphone Apple di Indonesia Dengan Menggunakan Metode Backpropagation - Abet Nego Situmorang; Fathur Dwi Putra; Jumanto Geogan Simanjuntak; P Poningsih (LPPM STIKOM Tunas Bangsa, 2022)
A system to predict the sales level of Apple branded smartphones in Indonesia. Artificial Neural Network is a method capable of performing mathematical processes to predict the sales level of Apple branded smartphones in Indonesia. Using the backpropagation method, the previous data processing is carried out to be used as input to predict the sales level of Apple smartphones in Indonesia. The data processed as variables are Apple Vendor Market. The data was taken from April 2021 to March 2022. April 2021 to September 2021 is used as input data, while October 2021 to March 2022 is used as target data. Several steps of Backpropagation are by initializing data, activation, calculating input data and output bias and data and bias changes. Those stages will obtain an output that will be achieved by having the smallest error value so that the prediction of the sales level of Apple branded smartphones in Indonesia is obtained. The training and testing process uses the Matlab 2018b tool. The result is a prediction with the training and testing process produces actual ouput as the target achieved.